2003
DOI: 10.1016/s1010-7940(03)00495-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical results of patients with a functional single ventricle

Abstract: This study revealed that the overall survival was disappointing and there were still problems that need to be solved in the pre-Fontan stage to improve the overall survival. The role of BCPS was not to contribute to the longer survival after Fontan operation, but to lower mortality in the pre-Fontan stage, which can offer a higher probability to proceed to the Fontan procedure successfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 17 publications
1
32
1
1
Order By: Relevance
“…However, the treatment of patients with functional single ventricle and total anomalous pulmonary venous connection (TAPVC), especially obstructed TAPVC, has remained a clinical challenge [1]. The majority of patients with functional single ventricle and TAPVC have heterotaxy syndrome with right atrial isomerism (RAI), which may contribute to a poor prognosis [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the treatment of patients with functional single ventricle and total anomalous pulmonary venous connection (TAPVC), especially obstructed TAPVC, has remained a clinical challenge [1]. The majority of patients with functional single ventricle and TAPVC have heterotaxy syndrome with right atrial isomerism (RAI), which may contribute to a poor prognosis [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…treatment were not applied (9). Considerable improvement in the surgical management of hypoplastic left heart syndrome (HLHS) has been repeatedly reported (5,6,10 -12), but it is unclear whether progress has been limited to this specific condition.…”
mentioning
confidence: 99%
“…Similar series at both the University of Michigan [5] and the University of Utah [10] have also reported good results in performing the staged Fontan operation with an operative mortality rate of less than 8%. Lee and colleague in their study have found a lower actuarial mortality (16.3 vs. 41.3%, p, 0:001) for the Fontan operation in the group in which the Fontan procedure was finished via Bidirectional Cavopulmonary Shunt (BCPS) than in the group finished without BCPS [11]. Masuda et al [7] reported a lower mortality and the higher probability to complete the Fontan procedure when using a preliminary [12] in their study of 75 patients have found higher mortality of 14.2% vs. 7.4% in the group of two stage TCPC than in the primary TCPC group.…”
Section: Discussionmentioning
confidence: 94%